Reproducibility of electronic tooth colour measurements - Ratzmann, Anja; Klinke, Thomas; Schwahn, Christian; Treichel, Anja; Gedrange, Tomasz (Biomedizinische Technik, 2008)
Clinical methods of investigation, such as tooth colour determination, should be simple, quick and reproducible. The determination of tooth colours usually relies upon manual comparison of a patient's tooth colour with a colour ring. After some days, however, measurement results frequently lack unequivocal reproducibility. This study aimed to examine an electronic method for reliable colour measurement. The colours of the teeth 14 to 24 were determined by three different examiners in 10 subjects using the colour measuring device Shade Inspector™. In total, 12 measurements per tooth were taken. Two measurement time points were scheduled to be taken, namely at study onset (T 1 ) and after 6 months (T 2 ). At either time point, two measurement series per subject were taken by the different examiners at 2-week intervals. The inter-examiner and intra-examiner agreement of the measurement results was assessed. The concordance for lightness and colour intensity (saturation) was represented by the intra-class correlation coefficient. The categorical variable colour shade (hue) was assessed using the kappa statistic. The study results show that tooth colour can be measured independently of the examiner. Good agreement was found between the examiners.